2020
DOI: 10.1111/ene.14358
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete or failed thrombectomy in acute stroke patients with Alberta Stroke Program Early Computed Tomography Score 0–5 – how harmful is trying?

Abstract: Background and purpose It is currently unknown whether mechanical thrombectomy (MT) for ischaemic stroke patients with low initial Alberta Stroke Program Early Computed Tomography Score (ASPECTS) is clinically beneficial or even harmful. The purpose of this study was to investigate whether failed or incomplete MT in acute large vessel occlusion stroke with an initial ASPECTS ≤ 5 is associated with worse clinical outcome compared to patients not undergoing MT. Methods This observational cohort study included a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Among 1166 studies obtained, finally 14 studies with 2547 patients fulfilled our eligibility criteria (Figure 1). Of the total 14 studies consisting of 19 trials, 11 studies were cohort studies (2 obtained 7 scores in NOS, 14,15 5 obtained 8 scores in NOS 1620 and 4 obtained 9 scores in NOS 8,2123 ) 1 study 24 was matched case-control study (9 scores in NOS) and the remaining 2 were secondary analysis of 7 randomized controlled trials. 6,7 The study characteristics were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 1166 studies obtained, finally 14 studies with 2547 patients fulfilled our eligibility criteria (Figure 1). Of the total 14 studies consisting of 19 trials, 11 studies were cohort studies (2 obtained 7 scores in NOS, 14,15 5 obtained 8 scores in NOS 1620 and 4 obtained 9 scores in NOS 8,2123 ) 1 study 24 was matched case-control study (9 scores in NOS) and the remaining 2 were secondary analysis of 7 randomized controlled trials. 6,7 The study characteristics were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies were conducted between 2016 and 2020 with the sample size ranging from 56 to 743. Overall, 9 studies 7,1519,2123 considered large ischemic core as low aspects and 3 studies 6,14,24 regarded it as large core volume, along with 2 studies 8,20 defined it as low aspects and/or large core volume (Table 1). In addition, 3 studies 8,18,23 used NCCT to evaluate ASPECTS, 3 studies 1921 used DWI, 2 studies 7,22 used NCCT or DWI,1 study 16 used CBV, 1 study 15 used CTASI, and one study had no clear definition to it.…”
Section: Resultsmentioning
confidence: 99%
“…However, nonrandomized studies and meta-analyses evaluating the clinical benefit of MT in patients with low ASPECTS have mixed results, with some studies demonstrating improvement after MT even in patients with incomplete or failed recanalization, while others suggest MT is not beneficial in patients with low ASPECTS. 13 , 22 25 …”
Section: Discussionmentioning
confidence: 99%
“…Good and very poor functional outcomes were defined as mRS 0-2 and mRS 5-6, respectively. [16][17][18][19][20] The mRS was evaluated at the 90-day follow-up by a physician or a trained and certified mRS nurse. sICH was defined according to the second European-Australasian Acute Stroke Study (ECASS II) as presence of intracerebral hemorrhage and a four-point neurological deterioration on the NIHSS.…”
Section: Study Cohortmentioning
confidence: 99%
“…The median ASPECTS was 4 (IQR 3-5), the median time from symptom onset to imaging was 119 min (IQR 79-157 min), and the median NIHSS was 18 (IQR [15][16][17][18][19][20][21][22]. A total of 290 patients (68%) received IVT and 168 patients (39%) underwent MT.…”
Section: Study Cohortmentioning
confidence: 99%